Predicting Emerald Ash Borer Adult Emergence and Peak Flight Activity in Winnipeg, Manitoba, Canada - MacDonald, Brett; Baydack, Rick; Westwood, A. Richard; Walker, David (Frontiers in Ecology and Evolution, 2022)
The invasive emerald ash borer (Agrilus planipennis Fairmaire; Coleoptera: Buprestidae) has killed tens of millions of ash (Fraxinus spp.) trees across North America. A. planipennis was first detected in Winnipeg, Manitoba in 2017 and has the potential to become a serious threat to the city’s ash canopy which accounts for approximately 30% of the public tree inventory. The goal of this study was to predict when adult A. planipennis emergence and peak activity would occur in Winnipeg to help logistical planning for the implementation of a city-wide management program. The management program would focus on detection and limiting the spread of the beetle with the objective of preserving ash trees as long as possible allowing for more proactive management of the EAB infestation. To predict adult emergence and peak activity of A. planipennis, we used local weather station data to calculate the number of degree-days accumulated in each year for the 1970-2019 period using three different degree-day accumulation models. Developmental thresholds for A. planipennis were derived from previous North American studies. The estimated mean emergence dates for the 50-year period were June 14 ±8.5 days (double sine model), June 14 ± 8.5 days (single sine model), and June 19 ± 9.1 days (standard model) whereas the peak activity dates were July 16 ± 8.8 days (double sine model), July 17 ± 8.7 days (single sine model), and July 21 ± 9.4 days (standard model). Meteorological records indicate that temperatures in the Winnipeg region have increased over the study period. However, our predicted emergence dates do not significantly differ over the 50 years examined in the study, although estimated peak activity dates are significantly earlier, suggesting that EAB movement may benefit from climate change. The results from this study will provide managers with information regarding the temporal behaviour of A. plannipennis in Winnipeg allowing for improved timing of control measures and monitoring, thereby extending the projected life span of a significant ash tree population within the Winnipeg urban region. The management model developed for Winnipeg could serve as an example for other locations in the prairie region of North America.